How Social Preferences Shape Incentives in (Experimental) Markets for Credence Goods - Kerschbamer, Rudolf (John Wiley and Sons Inc., 2016)

(untitled) (Econ J (London))
Credence goods markets suffer from inefficiencies caused by superior information of sellers about the surplus‐maximising quality. While standard theory predicts that equal mark‐up prices solve the credence goods problem if customers can verify the quality received, experimental evidence indicates the opposite. We identify a lack of robustness with respect to heterogeneity in social preferences as a possible cause of this and conduct new experiments that allow for parsimonious identification of sellers’ social preference types. Our results confirm the assumed heterogeneity in social preferences and provide strong support for our explanation of the failure of verifiability to increase efficiency.